Do Europeans like nudges? - Reisch, Lucia A.; Sunstein, Cass R. (Judgment and Decision Making, 2016)
In recent years, many governments have shown a keen interest in “nudges” — approaches to law and policy that maintain freedom of choice, but that steer people in certain directions. Yet to date, there has been little evidence on whether citizens of various societies support nudges and nudging. We report the results of nationally representative surveys in six European nations: Denmark, France, Germany, Hungary, Italy, and the United Kingdom. We find strong majority support for nudges of the sort that have been adopted, or under serious consideration, in democratic nations. Despite the general European consensus, we find markedly lower levels of support for nudges in two nations: Hungary and Denmark. We are not, in general, able to connect support for nudges with distinct party affiliations.